Nuclear and optical dual-labelled imaging agents - Singh, G.; Gott, M.D.; Pietzsch, H.-J.; Stephan, H. (Nuklearmedizin - NuclearMedicine, 2016)
Over the last two decades, molecular imaging has been established as a valuable technology, aiming at visualization and characterization of biochemical processes on a molecular level in isolated cells, tissues and higher organisms. Within the wide scope of the various imaging techniques, dual-labelled modalities for nuclear (PET, SPECT) and near-infrared fluorescence (NIRF) imaging show promise owing to their comparable detection sensitivity. Novel materials offer excellent prospects for the development of new non-invasive strategies of early diagnosis and efficient monitoring of therapeutic treatments. In the field of cancer medicine, the combination of different imaging techniques such as PET/SPECT and OI for tracking down tumours and metastases, and subsequent image-guided surgery for tumour resection is particularly attractive.This review focuses on the development of promising dual-labelled agents to be applied in bimodal nuclear/optical imaging, combining radionuclides and fluorescent dyes. The discussion encompasses modular ligands as well as nanoscale systems, including antibodies and their fragments.
Keywords: Molecular imaging; PET; SPECT; fluorescence; dual labelling